SOME LIMITATIONS OF ENHANCED OIL RECOVERY IN INDONESIA - Herlan Adim (Scientific Contributions Oil and Gas, 1994)
Enhanced Oil Recovery (EOR) technologies are now being developed year by year. Some of technologies are already applied in pilot or commercial scale in actual oilfields. Meanwhile, conditions for the exploration of new oil fields are becoming more severe. Accordingly the qualification as being an operator in many oil companies is going to be justified in terms of their capability in EOR technology in addition to the capability of exploring new oil fields.